EVALUATION OF GROUNDWATER SUITABILITY FOR DOMESTIC AND IRRIGATIONAL PURPOSES IN NEWCASTLE, KWAZULU-NATAL, SOUTH AFRICA - Nolakana, Pamela; Siad, Abdi; Solomon, Henok (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study was conducted in Newcastle, in the KwaZulu-Natal province of South Africa. In order to evaluate the quality of groundwater in study area, 31 samples were collected. The samples were analysed for Magnesium (Mg2+), Calcium (Ca2+), Sodium (Na+), Potassium (K+), Chloride (Cl-), Sulfate (SO42-), Bicarbonate (HCO3-), Nitrate (NO3-), Fluoride (F-) (pH, TDS and Ec. The South African Quality Water Guidelines (SAQWG) and the World Health Organization (WHO) water standards were used as the basis of evaluating the suitability of groundwater for drinking purposes. Electrical Conductivity (EC), Sodium Percent (Na %), Sodium Adsorption Ratio (SAR), Residual Sodium Carbonate (RSC), Kelly's Ratio (KR), Magnesium Ratio (MR) and Permeability Index (PI) were used to evaluate suitability for irrigation. The spatial distribution of the results was presented using ArcGIS. The groundwater was found to be generally alkaline, soft to hard and fresh to brackish in nature. The order of abundance of major ions in the groundwater, based on their mean values is as follows: Na+>Ca2+>Mg2+>K+ and HCO3->SO42->Cl->NO3-.
Keywords: Groundwater; SAQWG; suitability; domestic; irrigation